Occurrence, formation and environmental fate of polycyclic aromatic hydrocarbons in biochars - Emmanuel Stephen Odinga; Fredrick Owino Gudda; Michael Gatheru Waigi; Jian Wang; Yanzheng Gao (Fundamental Research, 2021)
Biochar application for soil and agro-environmental development has attracted great attention due to its numerous advantages: improving the soil, mitigating greenhouse gas emissions, increasing crop productivity, and augmenting soil carbon storage. However, during the pyrolytic conversion of waste biomass, polycyclic aromatic hydrocarbons (PAHs), a category of toxic organic pollutants, are inescapably generated and linger on the residual solid coproduct called biochar. Therefore, it is crucial to assess the environmental persistence, bioavailability, effects of biochar-borne PAHs on plant growth and soil microbial community dynamics, food safety, and human health after application into soils. This review highlights the basic need to unravel critical mechanisms driving PAH formation in biochar and the dynamics between the sorbent (biochar) and soil microbes, along with the possible mitigation strategies. Current research gaps, including the influence of biochar application on the short and long-term fate of PAHs, as well as the proper control measures for biochar quality and associated risks, will be discussed herein. The key research findings from this script will lead to proposals in technological and quality control measures during biochar production to ensure they are clean and safe.